Greco-Latin Square Design for Selection of Excipients in the Development of Metformin Orodispersible Tablets - Mariana, Demchuk (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: To provide the patient with the most convenient mode of administration, there is a need to develop fast-disintegrating tablets, which disintegrate and dissolve rapidly in the saliva, within a few seconds without drinking water. The aim of this study was to analyze the influence of the groups of excipients on technological parameters of metformin orodispersible tablets (ODTs). Materials and Methods: Greco-Latin squares design was used to establish the relations between independent variables such as type of disintegrant, type of diluent, type of sugar-based excipients, type of lubricant, and dependent variables. Results: Orally disintegrating tablets of metformin were prepared by direct compression method. Studying different groups of excipients, it was found that they provide good values of pre-compression parameters of powder mixture and uniformity of weight of tablets. The usage of excipients has provided lower disintegration time (<3 min) and wetting time of tablets. Conclusion: Using Greco-Latin squares design, the influence of four groups of excipients on technological characteristics of metformin ODTs was evaluated. According to the results of desirability function, the best values of technological parameters of metformin ODT were obtained when adding Polyplasdone XL-10 crospovidone, microcrystalline cellulose (MCC) Sanaq Â®burst, MCC VivapurÂ® 200, lactose monohydrate, and Tablube Magnesium Stearate grade Micronized Vegetable to the tablets.